2015
DOI: 10.1002/macp.201500339
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solutions of Poly[2‐(N‐morpholino)ethyl methacrylate]: Learning about Macromolecular Aggregation Processes from a Peculiar Three‐Step Thermoresponsive Behavior

Abstract: Aqueous solutions of narrowly distributed poly[2‐(N‐morpholino)ethyl methacrylate], a biocompatible multiple stimuli‐responsive polymer, show a peculiar three‐step aggregation behavior upon heating, an effect which has hitherto barely been reported for other polymers. The phenomenon is discussed in terms of mesoglobule formation (first step) as well as by an unusual distinct disruption of hydrophobic hydration (second step) and hydrogen bonding to the hydrophilic aggregate surface (third step). Macroscopic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…In a conventional free radical polymerization, the chains can present a strong chain-to-chain deviation of composition, which results in different phase transitions. 1,37 The synthesis route of this research is an optimized work based on the research of Lutz et al 55 and Matyjaszewski et al 6 Lutz et al reported a well-controlled ATRP of OEOMAs in pure ethanol. The polarity of ethanol establishes fast polymerization kinetics, 55 but since OEOMA monomers have a slight polarity, their polymerization can also be successfully done in apolar solvents like anisole as reported by Matyjaszewski's group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a conventional free radical polymerization, the chains can present a strong chain-to-chain deviation of composition, which results in different phase transitions. 1,37 The synthesis route of this research is an optimized work based on the research of Lutz et al 55 and Matyjaszewski et al 6 Lutz et al reported a well-controlled ATRP of OEOMAs in pure ethanol. The polarity of ethanol establishes fast polymerization kinetics, 55 but since OEOMA monomers have a slight polarity, their polymerization can also be successfully done in apolar solvents like anisole as reported by Matyjaszewski's group.…”
Section: Resultsmentioning
confidence: 99%
“…34,[72][73][74][75] Salts are well-known to have a high impact on the behavior of thermoresponsive polymers in solution. 37 Both the cation and anion in the salt are considered to influence the solubility behavior of the macromolecules. 71 To study the effect of different anions on the solubility behavior of gradient and random copolymers, sodium salts of these anions are used.…”
Section: Effect Of Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the large variety and complexity of still regularly unpredictable stimuli‐related behavior makes fundamental research on the underlying mechanisms very important to date. Just to name a few, ongoing debates are held on cononsolvency phenomena, salting‐in and salting‐out effects, stimuli‐triggered aggregation mechanisms, and on the origins of upper and lower critical solution temperature‐type (UCST‐ and LCST‐type, respectively) behavior . Further remarkable research goes into the direction of time‐programmed stimuli‐responsive self‐assembly and superfast actuation …”
Section: Introductionmentioning
confidence: 99%